2011
DOI: 10.1007/s00432-011-1012-2
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of T-cell immune responses and signal transduction proteins in oral cancer patients: potential for IL-2-mediated immunotherapy

Abstract: The results suggest IL-2 to augment T-cell responses in a proportion of oral cancer patients with poor response to conventional therapy. IL-2 immunotherapy can be thought of as a personalized adjuvant therapy for oral cancer following the in vitro identification of IL-2 responders using the expression of TCRζ and ZAP-70 as biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…It directly promotes the transcription of FoxP3 [ 28 , 29 ]. Moreover, IL-2 has been shown to augment TCR-ζ (CD247) expression in chronic inflammation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…It directly promotes the transcription of FoxP3 [ 28 , 29 ]. Moreover, IL-2 has been shown to augment TCR-ζ (CD247) expression in chronic inflammation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…None of our previous studies analyzed the impact of an altered methylation pattern of these genes obtained from pre-operative oral brushing samples on post-surgical clinical outcome. Recently, few studies from other authors demonstrated that genetic and epigenetic alterations of some genes of our 13-gene panel may play a role in OSCC prognosis, presence of metastasis and response to treatment [18,[21][22][23][24][25][26]. For example, Marsit et al, starting from a case series of 68 post-surgical Formalin Fixed Paraffin Embedded (FFPE) OSCC samples revealed that an altered methylation pattern of ZAP70 and GP1BB is associated with poor survival [18].…”
Section: Introductionmentioning
confidence: 99%